Atiyah and Adams' sale of goods - Twigg-Flesner, Christian, 1957-; Canavan, Rick, 1957-; Atiyah, P.S.; Adams, John, 1975- (New York: Pearson, 2021)
'Once more, we were delighted to take on the task of updating this text for its 14th edition, having taken over editorial responsibilities from the late John Adams from the 13th edition. In our preface to the previous edition, we recorded the sudden passing of Professor Adams. Sadly, in this preface, we must note another passing: on 30 March 2018, Patrick Atiyah, who wrote the 1st-8th editions of this book and continues to give the book its name, passed away at the age of 87. Patrick was one of those giants of academic contract law whose contributions continue to be read and to inspire scholars everywhere. We are both mindful of our task to maintain the scholarly rigour which he gave to this book as we take it into the future. This edition is also the first time since the 9th edition without a Scottish editor. Professor Hector MacQueen had been responsible for adding Scottish content since the 10th edition (2001), but decided that he would discontinue this role after the 13th edition was published in 2016. We are very grateful for Hector's contributions to the work. On the advice of the book's publishers, this edition has been put together without the benefit of a Scottish editor, although we have, of course, continued to take decisions from the Scottish courts into account in updating the various chapters. Since the last edition was published, there have been few major developments in the law on the sale of goods, aside from the difficult ruling by the Supreme Court in PST Energy 7 Shipping LLC v OW Bunker Malta Ltd [2016] UKSC 23 (which arrived too late for proper consideration in the previous edition). We have updated the text in light of recent cases and academic writings where appropriate. Furthermore, we have continued our task of streamlining the running order of the chapters, and we have sought to make gentle updates to the language of the book, preserving its rigour but ensuring it remains accessible to a contemporary audience. In some instances, we have curtailed or removed altogether the detailed discussion of the pre-1994 case-law which had become redundant as a result of the changes made to the Sale of Goods Act at that time. The rise of digital technology and new business models in the digital economy will invariably have an impact on the law concerning the sale of goods, but at this point, the real impact is not yet known. In some places, we have alluded to the possible significance of digital technology, and this could well become a more significant theme in future editions'--
Sources of the law of sale of goods -- The contract of sale -- Subject-matter of the contract -- The types of obligation created -- The existence of the goods and the duty to pass a good title -- The duty to deliver the goods -- The duty to supply the goods at the right time -- The duty to supply goods in the right quantity -- The duty to supply goods od the right quality -- Exclusion of seller's liability -- The duties of the buyer -- The transfer of property -- Risk and frustration -- Transfer of title by a non-owner -- Export sales -- International Convention on Sales of Goods ('CISG') -- Real remedies -- Personal remedies -- Rejection of the goods, rescission, and specific performance -- Action for damages -- Consumer sales contracts -- Product liability -- Manufacturers' guarantees.
Puan Shaizimah Badzri (Bacaan Asas FUU)/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216390/ OC/ Bookline Services
Includes bibliographical references and index. (535-553 pages)
Keywords: Sales -- England; Sales -- Scotland; Sales -- European Union countries